FENOMENA ALIH KODE DAN CAMPUR KODE DALAM VIDEO PODCAST DEDDY CORBUIZER DAN AGNEZ MONICA: KAJIAN SOSIOLINGUISTIK - Nisa, Nurul; Nuryeti, Rita; Santoso, Damar Aji; Putri, Friska Ciptasari; Muasomah; Mukhlis, Abdul (CV. Kalimasada Group, 2025)
This study aims to examine the phenomenon of code-switching and code-mixing in digital interactions through the analysis of Deddy Corbuzier's podcast episode with Agnez Monica entitled “VIDI: OM balding, AGNEZ MO LOE CELINGKUH1N⁉️DAH G11L444 YA LOE OM